2015
DOI: 10.1177/1756287215574480
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, observational grouped analysis to evaluate the effect of triptorelin on lower urinary tract symptoms in patients with advanced prostate cancer

Abstract: Objectives: Few studies have assessed the effect of gonadotropin-releasing hormone (GnRH) agonists, such as triptorelin, on lower urinary tract symptoms (LUTS) in patients with advanced prostate cancer. Therefore, multiple, national observational, noninterventional studies were initiated to assess the effectiveness of triptorelin in reducing moderate or severe LUTS [International Prostate Symptom Score (IPSS) >7] in men with prostate cancer starting triptorelin therapy in clinical practice. Methods: Prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 21 publications
(43 reference statements)
1
22
0
1
Order By: Relevance
“…However, in another study, reductions in IPSS were greater in patients treated with the GnRH antagonist degarelix than in those receiving the combination of goserelin and bicalutamide . Recent non‐interventional studies have suggested an improvement in LUTS induced by triptorelin, as measured by the IPSS . In one study, mean total IPSS was reduced from 18.2 (95% CI 17.8–18.5) at baseline to 11.9 (95% CI 11.5–12.3; P < 0.001) and 10.6 (95% CI 10.2–11.0; P < 0.001) at weeks 24 and 48, respectively .…”
Section: Discussionmentioning
confidence: 96%
“…However, in another study, reductions in IPSS were greater in patients treated with the GnRH antagonist degarelix than in those receiving the combination of goserelin and bicalutamide . Recent non‐interventional studies have suggested an improvement in LUTS induced by triptorelin, as measured by the IPSS . In one study, mean total IPSS was reduced from 18.2 (95% CI 17.8–18.5) at baseline to 11.9 (95% CI 11.5–12.3; P < 0.001) and 10.6 (95% CI 10.2–11.0; P < 0.001) at weeks 24 and 48, respectively .…”
Section: Discussionmentioning
confidence: 96%
“…Up to 40% of men with localized prostate cancer may have moderate or severe lower urinary tract symptoms (LUTS) [ 48 ], but data on the impact of ADT on LUTS are limited [ 49 51 ]. Recently, the preliminary results of an observational study in six countries suggested that treatment with triptorelin 1- and 3-month formulations improved LUTS after 6 and 12 months, as measured by a significant reduction in the International Prostate Symptom Score (IPSS) [ 52 ]. Interestingly, the improvement in LUTS after triptorelin therapy, correlated with reductions in PSA levels [ 52 ].…”
Section: Triptorelin As Adtmentioning
confidence: 99%
“…Recently, the preliminary results of an observational study in six countries suggested that treatment with triptorelin 1- and 3-month formulations improved LUTS after 6 and 12 months, as measured by a significant reduction in the International Prostate Symptom Score (IPSS) [ 52 ]. Interestingly, the improvement in LUTS after triptorelin therapy, correlated with reductions in PSA levels [ 52 ]. Similar results were observed in a prospective observational study that included 325 Belgian patients with locally advanced or metastatic prostate cancer, the majority of whom (62%) had moderate (IPSS 8-19) to severe (IPSS ≥ 20) LUTS at study entry [ 53 ].…”
Section: Triptorelin As Adtmentioning
confidence: 99%
See 2 more Smart Citations